Aspergillus nosocomial infections Do cryptic species found in hospital environment matter? - Sabino, Raquel (2017)
Purpose: Aspergillus is a major threat causing nosocomial infections in immunocompromised patients. Advances in molecular methods allowed species identification through sequencing of specific genes, allowing high discrimination amongst isolates. Different Aspergillus species have different susceptibilities to antifungals and several cryptic species have been described as less susceptible to specific antifungals. Therefore, we addressed the possible influence of hospital environmental isolates in the overall situation of Aspergillus antifungal resistance. Methods: During one year, 101 air and 99 surface samples were collected from the environment of a Portuguese central hospital of Lisbon. Aspergillus isolates were identified morphologically and by molecular methods. Genomic DNA was prepared from each isolate and then sequenced to achieve the correct species identification. Determination of the antifungal susceptibility of selected isolates was performed by microdilution (CLSI M38-A2). The antifungal agents studied were deoxycholate amphotericin B, itraconazole, voriconazole, and posaconazole. Results: From the 200 samples collected, 75 isolates of Aspergillus were obtained and identified to section by ITS sequence; cryptic species were identified by β-tubulin and calmodulin sequencing. Ten different sections within the Aspergillus genus were identified: Versicolores (N=20), Nigri (N=11), Flavi (N=10), Circumdati (N=10), Fumigati (N=8), Usti (N=4), Terrei (N=4), Nidulantes (N=4), Aspergilli (N=3) and Cremei (N=1). From these, 25 different Aspergillus species were identified by β-tubulin and calmodulin sequencing, and a high percentage of cryptic species (not sensu stricto) was found (59%). Sections Usti, Versicolores and Circumdati harbored the highest proportion of cryptic species [100% (4/4), 95% (19/20) and 90% (9/10), respectively]. From the 75 isolates, 22 were tested for their antifungal susceptibility. Of the 8 Fumigati isolates, there was 1 cryptic species. The Circumdati, Versicolores and Nigri complexes contained isolates of cryptic species with reduced susceptibility to some of the antifungals used in clinical therapeutics. In the Circumdati complex, 3/5 isolates hadMIC to amphotericin B >8μg/ml and 1/5MIC >8μg/ml to itraconazole; 1/6 isolates fromVersicolores complex hadMIC to itraconazole >8 μg/ml; all 4 isolates fromNigri complex hadMIC to itraconazole=4 μg/ml. Conclusion: Since Aspergillus infections aremainly nosocomial, knowledge of themolecular epidemiology and determinationof the susceptibility profile of environmental isolateswould suggestmeasures need to be considered.